How can experiences of environmental education at the Maretlwane Wilderness School result in transformative learning? - Jones, Samantha (My University, 2018)
3 Abstract The aim of this study was to determine the extent to which experiences of environmental education at the Maretlwane Wilderness School resulted in transformative learning for the participants. The research question was if the Wilderness School experience could result in changes in perceptions and behaviours toward the environment, in other words did transformative learning occur. The participants of this case study were 14 and 15-year-old boys from St. John’s College who attended a month-long Wilderness School in the Magaliesberg. The boys were asked to complete questionnaires and participate in focus groups. The staff at the Wilderness School and parents of the participants were also given questionnaires to complete. The findings of this case study are that environmental education can result in transformative learning, however, if the changes are to be long term then ‘bridges’ need to be built connecting the different places of environmental learning and living. The natural environment where environmental education experiences take place need to be linked to the urban schools and homes of the participants. This research is important as Environmental Education is often seen as a way of addressing the environmental challenges that society faces today, however, it needs to be environmental education of a particular kind if we want to see changes in the way that people interact with the world around them. It is hoped that this study will inform educators and practitioners of environmental education so that programs can be improved upon and result in environmentally literate citizens that can participate in their communities.
School of Geography, Archaeology and Environmental Studies University of the Witwatersrand, Johannesburg South Africa, 2018
Keywords: Environmental education--Curricula; Curriculum planning